Sistem Informasi Keuangan Pada Universitas Negeri Gorontalo Berbasis Android - irfan abbas (Jurnal Informatika Upgris, 2019)
Abstract: In the Director General Regulation of the Treasury NumberPER-47 / PB / 2014 concerning Technical Guidelines for Administration, Bookkeeping, and Accountability of Treasurers in Public Service Bodies and Verification and Monitoring of Treasurer Accountability Reports on Public Service Bodies in CHAPTER I (GENERAL PROVISIONS) Article 1 Paragraph 2 states that the Receiving Treasurer is a person appointed to receive, deposit, deposit, administer, and account for state revenue in the context of implementing the State Budget at the Office / Work Unit (Satker) of the State / Institution, and Article 6 states that the Public Service Agency, hereinafter abbreviated as BLU, is an agency in the environment the government is formed to provide services to the community in the form of the supply of goods and / or services sold without prioritizing profit and in carrying out their activities based on the principles of efficiency and productivity. In CHAPTER III (INTRODUCTION BOOKING) Article 7 Paragraph 1 states that the Treasurer keeps records of all the money administered. The purpose of this research is to design and produce an Android-based Financial Information System so as to assist the Receiving Treasurer in inputting transactions until the accountability report information is in accordance with the Director General of Treasury Regulation Number PER-47 / PB / 2014. Based on the results of the discussion and making of the Financial Information System at the Gorontalo-based Android University, it can be concluded that the system has been completed and can be used. Financial Information System at Gorontalo State University Based on Android as a means of information about income reports at the BLU Gorontalo State University. Keywords: Information System, Treasurer BLU Receipt, Android